VARIASI POLA SIDIK JARI MASYARAKAT SUKU KAILI DAN SUKU TORAJA DI KOTA PALU DAN KABUPATEN SIGI, SULAWESI TENGAH - Gulo, Graciella Stevani; Junitha, I Ketut; Setyawati, Iriani (SIMBIOSIS, 2020)
A research on the variation of fingerprint patterns of Kailinese and Torajanese tribes have been done in Palu and Sigi Regency, Central Sulawesi. The aims of this research were to determine the variation of fingerprint patterns, Dankmeijer Index, Furuhata Index and Total Ridge Count of Torajanese and Kailinese. The population was divided into three groups, namely the Kaili Da'a (Kaili tribe which has phenotypic characteristics resembling the Australomelanesoid race), other Kaili groups and the Toraja tribe belonging to the Mongoloid race. The samples of fingerprints were taken by using the purposive sampling method with a total of 180 probandus, consisted of 60 people (30 males and 30 females) in each ethnic group. The tips of ten fingers were rubbed with paper that had contained 4B pencil rubbing, fingerprints were taken using clear tape and then the tape affixed on a probandus form. Data was analysed by Chi-square test and Student-t test. The fingerprint analysis showed that there were four fingerprint patterns found among the Kailinese and Torajanese tribes. The highest whorl frequency was found in the Torajanese at 50.17%, whereas Da'a and other Kaili groups had higher loop frequencies. Whorl type analysis showed simple whorl was the type most commonly found in all three populations. Furthermore, double loop whorl and the least frequency was the central pocket whorl. The Furuhata Index values ??for the Toraja, Kaili and Kaili Da'a tribes respectively were 102.73; 57,37; and 95.06 while the Dankmeijer Index values ??were 1.99; 5,61; and 2.77. The average of total ridge count in the Toraja, Kaili and Kaili Da'a tribes respectively were 134; 128.08 and 133.56.